2019
DOI: 10.1039/c9ra02792k
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional graphene networks and RGO-based counter electrode for DSSCs

Abstract: Graphene is considered to be a potential replacement for the traditional Pt counter electrode (CE) in dye-sensitized solar cells (DSSCs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…The EIS Nyquist plots are measured from high (1 MHz) to low (0.01 MHz) frequency at the V oc under one sun illumination (100 mW cm −2 ). The equivalent circuit model (Figure S3) includes the elements R S , R-CE , R-TiO 2 , and W S , representing the ohmic resistance of the FTO substrate ( R S ), interfacial charge-transfer resistance between the counter electrode and electrolyte ( R-CE ), interfacial charge-transfer resistance between the photoanode and electrolyte ( R-TiO 2 ), and the redox couple mass-transfer resistance ( W S , Warburg diffusion resistance) [40,41]. The electro-kinetic properties of the DSSCs are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The EIS Nyquist plots are measured from high (1 MHz) to low (0.01 MHz) frequency at the V oc under one sun illumination (100 mW cm −2 ). The equivalent circuit model (Figure S3) includes the elements R S , R-CE , R-TiO 2 , and W S , representing the ohmic resistance of the FTO substrate ( R S ), interfacial charge-transfer resistance between the counter electrode and electrolyte ( R-CE ), interfacial charge-transfer resistance between the photoanode and electrolyte ( R-TiO 2 ), and the redox couple mass-transfer resistance ( W S , Warburg diffusion resistance) [40,41]. The electro-kinetic properties of the DSSCs are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Preparation of GO, RGO and RGO/TiO 2 : GO was prepared by the modified Hummers' method. The optimized RGO samples were fabricated according to our previous works , . The RGO/TiO 2 composite is prepared by hydrothermal method.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, each parallel circuit combination from R1 to R4 is composed of double layer capacitance of different interface reactions. Tang et al reported rGO and 3D graphene network CE with an excellent PCE of 9.79% as a successful alternate to Pt CE to attain low‐cost and efficient PV devices . Owing to the attractive properties of graphene, Hsieh et al reported one‐dimensional carbon nanotubes (1D‐CNTs) and two‐dimensional graphene nanosheet (GNs) as a CE in DSSCs .…”
Section: Two‐dimensional Materials Based Counter Electrodementioning
confidence: 99%
“…Tang et al reported rGO and 3D graphene network CE with an excellent PCE of 9.79% as a successful alternate to Pt CE to attain low-cost and efficient PV devices. 92 Owing to the attractive properties of graphene, Hsieh et al reported one-dimensional carbon nanotubes (1D-CNTs) and two-dimensional graphene nanosheet (GNs) as a CE in DSSCs. 93 Figure 13D illustrates the schematic of CNT, and GNs-based CEs with star sign related to the sidewalls, nanosheets edges, and nanotube end.…”
Section: Graphene and Its Composites As Cementioning
confidence: 99%